Mechanical and Thermal Adsorption Actions on Epoxy Hybrid Composite Layered with Various Sequences of Alkali-Treated Jute and Carbon Fibre - R. Sasikumar; K. Venkadeshwaran; C. Ramesh Kannan; Melvin Victor De Poures; M. Aruna; N. Mukilarasan; Gopal Kaliyaperumal; Arundeep Murugan (Adsorption Science & Technology)
Structural applications are accomplished by using a lightweight epoxy matrix bonded with natural jute fibre/synthetic carbon fibre to enhance the physical, mechanical, and thermal properties obtained by different sequences of alkali-treated jute fibre (J.F.)/carbon fibre (C.F.) through conventional hand layup technique. The sequences of the sample are named as H1, H2, H3, and H4 layers of JF/JF/JF/JF, CF/CF/CF/CF, JF/CF/CF/JF, and CF/JF/JF/CF. Influences of JF/CF on physical, mechanical, and thermal adsorption properties of the epoxy composite are evaluated and compared. The mechanical tensile performance of the jute fibre-covered (JF/CF/CF/JF) composite H3 sample is augmented by 29% compared to the H4 sample. Similarly, the CF/JF/JF/CF combinations exhibited a higher impact strength of 129.71 KJ/m2. The maximum hardness of 47.12Hv was found on the four-layered carbon fibre. The thermal adsorption actions on developed composites are evaluated by thermogravimetric apparatus (TGA). It is confirmed that the presence of JF/CF in epoxy composites can endure stability at a higher temperature.